Pancreatic cancer: Cutaneous metastases, clinical descriptors and outcomes. (6th June 2022) - Gu, Lilly; Mehta, Paras P.; Rao, Devika; Rotemberg, Veronica; Capanu, Marinela; Chou, Joanne; Lin, Sabrina; Sigel, Carlie S.; Busam, Klaus J.; Boyce, Lindsay; Gordon, Allison; O'Reilly, Eileen M.
Abstract: Background: Cutaneous metastases in pancreatic cancer (PC) are rare. Herein, we evaluate the clinical, genomic, and other descriptors of patients with PC and cutaneous metastases. Methods: Institutional databases were queried, and clinical history, demographics, PC cutaneous metastasis details, and overall survival (OS) from cutaneous metastasis diagnosis were abstracted. OS was estimated using Kaplan–Meier methods. Results: Forty patients were identified, and median age (Q1–Q3, IQR) of PC diagnosis was 66.0 (59.3–72.3, 12.9) years. Most patients had Stage IV disease at diagnosis ( n = 26, 65%). The most common location of the primary tumor was the tail of the pancreas ( n = 17, 43%). The most common cutaneous metastasis site was the abdomen ( n = 31, 78%), with umbilical lesions occurring in 74% ( n = 23) of abdominal lesions. The median OS (95% CI) was 11.4 months (7.0, 20.4). Twenty‐three patients had umbilical metastases (58%), and 17 patients had non‐umbilical metastases (43%). The median OS (95% CI) was 13.7 (7.0, 28.7) months in patients with umbilical metastases and 8.9 (4.1, Not reached) months in patients with non‐umbilical metastases ( p = 0.1). Sixteen of 40 (40%) patients underwent somatic testing, and findings were consistent with known profiles. Germline testing in 12 (30%) patients identified pathogenic variants in patients: CHEK2, BRCA1, and ATM. Conclusion: Cutaneous metastases from PC most frequently arise from a pancreas tail primary site and most frequently occur in the umbilicus. Cutaneous metastases may generally be categorized as umbilical or non‐umbilical metastases. Abstract : Cutaneous Metastasis from Pancreatic Cancer. (A) pink, scaly, eroded papulonodule. (B) moderately to poorly differentiated adenocarcinoma in the dermis. (C) tumor cells are immunoreactive for cytokeratin 7.